Health Inequalities Among Korean Employees - Eunsuk Choi (Elsevier, 2017)
Background: Social status might be a determinant of occupational health inequalities. This study analyzed the effects of social status on both work environments and health outcomes. Methods: The study sample consisted of 27,598 wage employees aged 15 years and older from among the Korean Working Condition Survey participants in 2011. Work environments included atypical work, physical risks, ergonomic risks, work demands, work autonomy, social supports, and job rewards. Health outcomes comprised general health, health and safety at risk because of work, the World Health Organization-5 Well-being Index, work-related musculoskeletal disease, and work-related injury. Multivariable logistic-regression models were used to identify the associations between social status and work environments and health outcomes. Results: Employees in the demographically vulnerable group had lower occupational status compared with their counterparts. Low social status was largely related to adverse work environments. Especially, precarious employment and manual labor occupation were associated with both adverse work environments and poor health outcomes. Conclusion: Precarious and manual workers should take precedence in occupational health equity policies and interventions. Their cumulative vulnerability, which is connected to demographics, occupational status, adverse work environments, or poor health outcomes, can be improved through a multilevel approach such as labor market, organizations, and individual goals. Keywords: employee health, health equity, social status